Real Exchange Rate Misalignment and Trade Flows in Nigeria (1960-2013) (International Journal of Banking and Finance, 2016)
The paper examined the effects of real exchange rate misalignment on trade flows in Nigeria between the year 1960 and 2013. Trade flows were divided into export flow, import and trade balance. The paper employed the behavioural equilibrium exchange rate (BEER) approach to obtain the equilibrium real exchange rate for Nigeria and a single equation co-integration approach to determine the effect of exchange rate misalignment on trade flows. It was observed that Nigeria’s real effective exchange rate appreciated in most periods between 1960 and 1985 and depreciated in most periods between 1986 and 2013. The result of the study further indicates that real exchange misalignment has no significant effect on the volume of export but it has a significant depreciating effect on import and trade balance in the country. The study recommends a flexible exchange rate system to reduce real exchange rate misalignment and diversified export products to enable volume export responds to real exchange rate movements in the country.